Intravenous Clonidine versus Intraperitoneal Clonidine for Postoperative Analgesia After Total Abdominal Hysterectomy: A Randomised Controlled Trial - Gupta, Divya (Turk J Anaesthesiol Reanim, 2021)
OBJECTIVE: This prospective randomised double-blind study was conducted to compare the effect of intravenous (IV) with intraperitoneal (IP) administration of clonidine with respect to analgesic efficacy and side effects. METHODS: A total of 60 American Society of Anaesthesiologists (ASA) physical status class I and II patients, aged 35–60 years, undergoing total abdominal hysterectomy, were randomly divided into 2 groups. Standard general anaesthesia technique was used. All the patients in group IV received 3 μg kg(−1) of IV clonidine after resection of the uterus along with 0.25% bupivacaine (20 mL intraperitoneally and 10 mL as wound infiltration), whereas patients in group IP received 10 mL of normal saline intravenously and 3 μg kg(−1) of clonidine mixed with 0.25% bupivacaine (20 mL intraperitoneally and 10 mL as wound infiltration). Postoperative analgesia was provided with IV diclofenac every 8 hours and IV fentanyl (1 μg kg(−1)) on demand. Pain at rest, opioid consumption, level of sedation and severity of nausea were recorded for 24 hours. The heart rate (HR) and blood pressure (BP) were recorded at an interval of 15 minutes for 2 hours followed by routine hourly monitoring. RESULTS: Both the groups were found to be similar with respect to demography and ASA physical status. The maximum pain was felt at 6 hours in both the groups. The mean visual analogue scale score at 6 hours (p=0.47) was comparable. However, patients in group IV had significantly higher sedation (p<0.001) and nausea (p=0.013) scores on arrival at post-anaesthesia care unit along with a significant reduction in HR (p=0.001) and BP (p=0001) for the first 2 hours postoperatively. CONCLUSION: Although IP clonidine is comparable with IV clonidine with respect to postoperative pain scores and supplementary opioid requirement, the side effects are significantly less with IP clonidine.